Perbandingan Pengaruh Latihan Rondo dan Wall Pass Terhadap Peningkatan Akurasi Passing Futsal Siswa Sekolah Dasar - Shiddiq Saeful Rohman; Aam Ali Rahman; Entan Saptani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to compare the effects of rondo and wall pass training on improving futsal passing accuracy in elementary school students. The method used was a quasi-experimental pretest-posttest design, with research subjects divided into two treatment groups: the rondo training group and the wall pass training group, and a control group given paired passing treatment. The research instrument was a passing accuracy test conducted before and after the treatment, while data analysis included normality tests, homogeneity tests, and hypothesis tests. The results showed that both training methods had a significant effect on improving passing accuracy, but wall pass training was more effective than rondo training because it emphasized more on technical repetition and consistency, while rondo focused more on game aspects and teamwork. Thus, it can be concluded that wall pass training is more effective in improving futsal passing accuracy in elementary school students, although both methods can be combined to optimize technical and tactical abilities. Keyword: Futsal Passing, Rondo, Wall pass